The New Zealand Blood Donors' Health Study: baseline findings of a large prospective cohort study of injury. (1st March 2002) - Ameratunga, S N; Norton, R N; Whitlock, G; MacMahon, S; Coggan, C; Jackson, R T; Langley, J D; Parag, V; Smith, D; Woodfield, D G
Abstract : Introduction: Cohort studies have contributed important scientific knowledge regarding the determinants of chronic diseases. Despite the need for etiologic investigations, this design has been infrequently used in injury prevention research. Objectives: To describe the baseline findings of the New Zealand Blood Donors' Health Study, a large prospective study designed to investigate relationships between lifestyle, psychosocial factors, and serious injury due to road crashes, falls, self harm, assault, work, sport, and recreation. Methods: Participants were recruited from fixed and mobile collection sites of a voluntary non-profit blood donor program. Baseline exposure data (for example risk taking behaviors, alcohol and marijuana use, sleep habits, and depression) were collected using a self administered questionnaire. Outcome data regarding serious injury will be collected prospectively through computerized record linkage of participants' unique identifiers to national morbidity and mortality databases. Results: In total, 22 389 participants enrolled in the study (81% response rate). The diverse study population included 36% aged 16–24 years, 20% rural residents, and large variability in exposures of interest. For example, in the 12 months before recruitment, 21% had driven a motor vehicle when they considered themselves over the legal limit for alcohol, and 11% had been convicted of traffic violations (excluding parking infringements). Twelve per cent had seriously considered attempting suicide sometime in their life. Conclusions: This is the first, large scale cohort study investigating determinants of serious injury in New Zealand and among the largest worldwide. Preliminary findings from prospective analyses that can inform injury prevention policy are expected within five years.